2022
DOI: 10.1083/jcb.202109134
|View full text |Cite
|
Sign up to set email alerts
|

ANKRD24 organizes TRIOBP to reinforce stereocilia insertion points

Abstract: The stereocilia rootlet is a key structure in vertebrate hair cells, anchoring stereocilia firmly into the cell’s cuticular plate and protecting them from overstimulation. Using superresolution microscopy, we show that the ankyrin-repeat protein ANKRD24 concentrates at the stereocilia insertion point, forming a ring at the junction between the lower and upper rootlets. Annular ANKRD24 continues into the lower rootlet, where it surrounds and binds TRIOBP-5, which itself bundles rootlet F-actin. TRIOBP-5 is misl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…Contrast was manually adjusted to retain both dim and bright structures due to the high dynamic range of the phalloidin signal. Verification of channel alignment and measurement of the microscope point-spread function was carried out as previously described [46].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrast was manually adjusted to retain both dim and bright structures due to the high dynamic range of the phalloidin signal. Verification of channel alignment and measurement of the microscope point-spread function was carried out as previously described [46].…”
Section: Methodsmentioning
confidence: 99%
“…Our measurements should reflect native lengths and widths; dimensions of mildly-fixed, phalloidin-labeled stereocilia are not significantly different from dimensions of live stereocilia labeled with membrane dyes [43]. We improved resolution over conventional confocal microscopy by using lattice structured illumination microscopy (lattice SIM) [44][45][46], which has a point-spread function (PSF) of ~150 nm under our conditions [46]; typical confocal microscopy PSFs are ~230 nm [47]. We rendered image surfaces from each phalloidin-stained hair bundle (Fig 1A -F); rendered surfaces are three-dimensional models of specific structures computed from stacks of images by pre-processing, segmentation, and connectedcomponent labeling steps.…”
Section: Quantitation Of Stereocilia Actin-core Dimensions Using Latt...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, localization of TRIOBP-1 was not previously investigated for lack of a TRIOBP-1–specific antibody since most of the sequence of TRIOBP-1 is identical to the C-terminal part of TRIOBP-5. We recently validated an anti-TARA antibody using our Triobp ΔEx9-10/ΔEx9-10 mice ( 29 ) and showed that the antibody signal in stereocilia rootlets solely represents the TRIOBP-5 isoform. Consequently, to investigate the correlation of our expression data of Triobp-1 , Triobp-4 , and Triobp-5 mRNAs with the corresponding protein isoform localizations, we used TRIOBP4/5-specific and anti-TARA antibodies in Triobp +/+ and Triobp ΔEx9-10/ΔEx9-10 mice.…”
Section: Resultsmentioning
confidence: 99%
“…P8 and P20 wild-type Triobp +/+ and homozygous Triobp ΔEx9-10/ΔEx9-10 mice were used for immunostaining of the organ of Corti with anti-TARA antibody (Proteintech, 16124-1-AP) which was developed against an antigen corresponding to the C-terminal sequence of TRIOBP-5 identical to TRIOBP-1, as reported ( 29 ). We also used antibodies against TRIOBP-4/5 and against TRIOBP-5 as previously described ( 9 , 10 ).…”
Section: Methodsmentioning
confidence: 99%